ENVIRONMENTAL IMPACT OF PHARMACEUTICALS: ANALYTICAL APPROACHES AND MITIGATION STRATEGIES - Hamid Javaid (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Pharmaceuticals, essential for human and animal health, are increasingly recognized as environmental contaminants. This research paper explores the environmental impact of pharmaceuticals, focusing on their occurrence, persistence, and effects in various ecosystems. It discusses advanced analytical techniques for detecting pharmaceutical residues in the environment and evaluates current and emerging mitigation strategies. The paper highlights the necessity for a multi-faceted approach involving improved waste management, advanced treatment technologies, regulatory frameworks, and public awareness to mitigate the environmental impact of pharmaceuticals.